Electrical stimulation promotes the wound‐healing properties of diabetic human skin fibroblasts. (20th April 2022) - Abedin‐Do, Atieh; Zhang, Ze; Douville, Yvan; Méthot, Mireille; Bernatchez, Julien; Rouabhia, Mahmoud
Abstract: This study evaluated the effect of low (20 and 40 mV/mm) intensities of electrical stimulation on the proliferation and migration of skin fibroblasts from diabetic donors. We also examined the effect of electrical stimulation on modulating the capacity of fibroblasts to contract collagen gel, express alpha‐smooth muscle actin, and secrete proteolytic enzymes involved in regulating extracellular matrix synthesis and degradation. Our study shows that 20 and 40 mV/mm of stimulation increased the growth of fibroblasts extracted from diabetic patients but not from non‐diabetic donors. Electrical stimulation increased the migration of diabetic fibroblasts, their capacity to contract collagen gel, and the expression of alpha‐smooth muscle actin and promoted different proteolytic enzymes involved in accelerating wound healing. Overall results confirm the effectiveness of electrical stimulation in modulating the wound healing activities of fibroblasts extracted from diabetic skin donors. This study, therefore, suggests the possible use of electrical stimulation to promote diabetic foot ulcer healing by stimulating the wound healing properties of skin fibroblasts.